Cardiac pacing : guidelines for cardiac pacing and cardiac resynchronization therapy (Vreckové odporúčania ESC, 2007)
The guidelines for the appropriate use of pacemaker devices presented in this document, a joint ESC and EHRA initiative, aim to provide for the first time in Europe an up to date specialists' view of the field. The guidelines cover two main areas: the first includes permanent pacing in bradyarrhythmias, syncope, and other specific conditions, while the second refers to ventricular resynchronization as an adjunct therapy in patients with heart failure.